2017
DOI: 10.3389/fpsyg.2017.00696
|View full text |Cite
|
Sign up to set email alerts
|

Testing Separability and Independence of Perceptual Dimensions with General Recognition Theory: A Tutorial and New R Package (grtools)

Abstract: Determining whether perceptual properties are processed independently is an important goal in perceptual science, and tools to test independence should be widely available to experimental researchers. The best analytical tools to test for perceptual independence are provided by General Recognition Theory (GRT), a multidimensional extension of signal detection theory. Unfortunately, there is currently a lack of software implementing GRT analyses that is ready-to-use by experimental psychologists and neuroscient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…In particular, the specific morphed face dimensions illustrated in Figure 1, and used in the present study, have been previously shown to be perceptually integral ahead of training according to a variety of tests (see . Evidence of the integrality of those specific dimensions comes from a strong Garner interference effect (Garner, 1974), a failure of marginal accuracy invariance, a failure of response time invariance, and a model-based analysis of data using general recognition theory (for reviews of these tests, see Soto et al, 2017). That is only the evidence showing integrality in the specific stimuli used here.…”
mentioning
confidence: 92%
“…In particular, the specific morphed face dimensions illustrated in Figure 1, and used in the present study, have been previously shown to be perceptually integral ahead of training according to a variety of tests (see . Evidence of the integrality of those specific dimensions comes from a strong Garner interference effect (Garner, 1974), a failure of marginal accuracy invariance, a failure of response time invariance, and a model-based analysis of data using general recognition theory (for reviews of these tests, see Soto et al, 2017). That is only the evidence showing integrality in the specific stimuli used here.…”
mentioning
confidence: 92%
“…There are two reasons to believe that the perceptual changes observed after categorization training with morphed faces and other objects are not due to readout mechanisms. First, the effects of categorization are not task-specific, but they transfer from a categorization task to unrelated tasks, both in psychophysical (e.g., Folstein et al, 2012b;Goldstone & Steyvers, 2001a;Soto et al, 2017) and neuroimaging (Brants et al, 2016;Folstein et al, 2013) studies. Readout is usually considered to be taskspecific, as different tasks are solved optimally using different sources of information.…”
Section: What About Changes In Readout?mentioning
confidence: 99%
“…Acquired equivalence is observed as a decrease in discriminability along the category-irrelevant dimension after categorization training. Relatedly, categorization training increases the separability or invariance of the category-relevant dimension , which means that changes in an irrelevant dimension do not interfere with perception of the category-relevant dimension, according to a variety of tests from multidimensional signal detection theory Soto et al, 2017). Category-Relevant Dimension Category-Irrelevant Dimension Category Boundary Figure 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fitting a GRT-wIND model and testing for perceptual separability, perceptual independence, and decisional separability can be done in R with the grtools package (R Core Team, 2014;Soto, Zheng, Fonseca, & Ashby, 2016; a general overview of GRT, as well as the specifics of the GRT-wIND analysis, are covered in greater detail in the Appendix). The model was fit using the grt_wind_fit_parallel() function with 200 repetitions (i.e., the model is fit 200 times and the function returns the parameters of the model with the best fit).…”
Section: Resultsmentioning
confidence: 99%